Occupational Disease and Public Health Concerns of Migrant Construction Workers: A Social Epidemiological Study in Western Uttar Pradesh. (March 2014) - Akram, Mohammad
The unorganised workers in the construction industry face several health hazards. The situation is doubly critical for the migrant construction workers (MCWs) due to congruence of their poor living and work environment. This is a cross-sectional study based on social epidemiological perspective. It studies the occupational disease, treatment patterns and other public health concerns of MCWs in urban spaces of western Uttar Pradesh. It uses semi-structured interview schedule and ethnographic observation during the fieldwork. The multi-stage cluster sampling is used to identify the required samples. Findings reveal that self-reported case of injury and disease among the MCWs in last one year is 35 per cent and 70 per cent, respectively. The public health facilities are missing in most of the construction sites. The migratory condition, narrow and unhygienic living space and lack of basic health facilities increase the burden of occupational diseases manifold on the migrant workers. Policy corrections are required not only for improving the conditions of migrant workers but also for removing disparities in economic and social development among the regions and states which will regulate the magnitude and direction of unproductive migration.